Bondholder governance, takeover likelihood, and division of gains - Akdoğu, Evrim; Paukowits, Aysun Alp; Celikyurt, Ugur (Journal of Corporate Finance, 2023)
We investigate the effect of creditor rights on the probability of becoming a takeover target by constructing firm-level bond covenant indices. Our primary result is that the more restrictive covenants a firm has, the more likely it is to become the target of an acquisition. This finding is robust to the exclusion of merger-related event-risk covenants which have the opposite impact and appear to reduce takeover likelihood. Furthermore, this effect is not driven by financially distressed firms and rather contained in small, profitable, financially healthy firms with high growth opportunities and low cash holdings. We also find that a higher target covenant index leads to a significant decrease (increase) in target (acquirer) abnormal returns around acquisition announcements and tilts merger gains towards the acquirer, suggesting the presence of a ‘covenant discount’ for potential target firms. Overall, our results are consistent with covenants creating key frictions, and in turn, making firms viable targets for acquirers with possibly deep pockets.